Fenofibrate Attenuates Renal Tubular Cell Apoptosis by Up-Regulating MCAD in Diabetic Kidney Disease - Tang C; Deng X; Qu J; Miao Y; Tian L; Zhang M; Li X; Sun B; Chen L (Dove Medical Press, 2023)
Chao Tang,1,2,* Xiaoqing Deng,1,* Jingru Qu,1 Yahui Miao,1 Lei Tian,1 Man Zhang,1 Xiaoyu Li,1 Bei Sun,1 Liming Chen1 1NHC Key Laboratory of Hormones and Development, Tianjin Key Laboratory of Metabolic Diseases, Chu Hsien-I Memorial Hospital & Tianjin Institute of Endocrinology, Tianjin Medical University, Tianjin, 300134, People's Republic of China; 2The Affiliated Huzhou Hospital, Zhejiang University School of Medicine (Huzhou Central Hospital), Huzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Liming Chen; Bei Sun, No. 6 North Huanrui Road, Beichen District, Tianjin, People's Republic of China, Email xfx22081@vip.163.com; sun_peipei220@hotmail.comBackground: Diabetic kidney disease (DKD) is a major diabetic microvascular complication. Fatty acid-induced lipotoxicity and apoptosis were associated with the exacerbation of DKD. However, the association of lipotoxicity with renal tubular apoptosis and the effects of fenofibrate on DKD are not fully understood.Methods: Eight-week-old db/db mice were given fenofibrate or saline by gavage for 8 weeks. Human kidney proximal tubular epithelial (HK2) cells stimulated with palmitic acid (PA) and high glucose (HG) were used as a model of lipid metabolism disorders. Apoptosis was assessed with or without fenofibrate. The AMP-activated protein kinase (AMPK) activator 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) and AMPK inhibitor Compound C were used to determine the involvement of AMPK and Medium-chain acyl-CoA dehydrogenase (MCAD) in the regulation of lipid accumulation by fenofibrate. MCAD silencing was achieved by small interfering RNA (siRNA) transfection.Results: Fenofibrate reduced triglyceride (TG) content and lipid accumulation in DKD. Importantly, renal function and tubular cell apoptosis were significantly improved by fenofibrate. Fenofibrate reduced apoptosis, accompanied by increased activation of the AMPK/FOXA2/MCAD pathway. MCAD silencing resulted in apoptosis and lipid accumulation despite fenofibrate treatment.Conclusion: Fenofibrate improves lipid accumulation and apoptosis through the AMPK/FOXA2/MCAD pathway. MCAD may be a potential therapeutic target of DKD, and the use of fenofibrate as a treatment for DKD warrants further study.Keywords: fenofibrate, diabetic kidney disease, renal tubular cell, apoptosis, lipid accumulation, MCAD